Organosolv pulping and paper properties on planted Acacia Hybrid of Sabah - Liew, Kang Chiang; Shirley Bakansing; Ag. Ahmad Moho. Yunus; Rafidah Md. Salim (Universiti Malaysia Sabah, 2010)
In this study, ethanol pulping process was done on Acacia hybrid wood chips at different ethanol concentrations. The pulps were screened, and later formed into handsheets before being prepared into test pieces for physical and mechanical evaluations. Besides that, the wood was examined for its chemcial compositions and morphological studies. Scanning electron microscopy was performed on the handsheets for its surface evaluation. Data gathered was statistically analysed. As a comparison, kraft pulps were produced. The expected outcome of the research study was that the pulp and paper properties of organosolv pulping process is comparable if not better than the kraft pulping process.